2004
DOI: 10.1111/j.1460-9568.2004.03255.x
|View full text |Cite
|
Sign up to set email alerts
|

Orexins (hypocretins) directly interact with neuropeptide Y, POMC and glucose‐responsive neurons to regulate Ca2+ signaling in a reciprocal manner to leptin: orexigenic neuronal pathways in the mediobasal hypothalamus

Abstract: Orexin-A and -B (hypocretin-1 and -2) have been implicated in the stimulation of feeding. Here we show the effector neurons and signaling mechanisms for the orexigenic action of orexins in rats. Immunohistochemical methods showed that orexin axon terminals contact with neuropeptide Y (NPY)- and proopiomelanocortin (POMC)-positive neurons in the arcuate nucleus (ARC) of the rats. Microinjection of orexins into the ARC markedly increased food intake. Orexins increased cytosolic Ca(2+) concentration ([Ca(2+)](i))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(142 citation statements)
references
References 87 publications
7
133
1
1
Order By: Relevance
“…Orexin-containing terminals are found on and around ARC POMC neurons Guan et al, 2001;Muroya et al, 2004), and the release of orexin is highest during active, awake periods (Kiyashchenko et al, 2002). Considering the appetite-suppressing influence of POMC neurons, their electrical inhibition by orexin, described here, may help to ensure that food seeking coincides with periods when the animal is most alert and active.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Orexin-containing terminals are found on and around ARC POMC neurons Guan et al, 2001;Muroya et al, 2004), and the release of orexin is highest during active, awake periods (Kiyashchenko et al, 2002). Considering the appetite-suppressing influence of POMC neurons, their electrical inhibition by orexin, described here, may help to ensure that food seeking coincides with periods when the animal is most alert and active.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of synaptic inputs to POMC neurons may thus be a general way for body weight-regulating compounds to modulate the activity of ARC POMC cells. Muroya et al (2004) showed that orexin reduced the intracellular Ca 2ϩ concentration of isolated POMC neurons, suggesting that orexin directly interacts with POMC neurons. In contrast, in our experiments, the effects of orexin on the firing rate of POMC cells appeared to be primarily "indirect," via modulation of synaptic inputs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After [Ca 2ϩ ]i measurements, the cells were fixed with 4% paraformaldehyde for 30 min. Immunocytochemical identification of POMC neurons was performed using rabbit anti-POMC antibody (34) and ABC method (20). For treatment with LY-294002 (SABiosciences), cells were treated with LY-294002 at 50 M for 30 min and stimulated with leptin and glutamate.…”
Section: Measurement Of Oxygen Consumption and Physical Activitymentioning
confidence: 99%
“…Electrophysiological studies have shown a possible involvement of the anorexigenic pro-opiomelanocortin (PoMC) system. Apart from exciting NPY-containing neurons [56,57] , orexin also inhibits PoMC-containing neurons in ] i levels [58,59] . intriguingly, the central orexinergic system may regulate feeding behavior through its innervation of the limbic system [60] .…”
Section: Feeding and Energy Homeostasismentioning
confidence: 99%